REVIEW ARTIKEL : TELAAH PENGOBATAN MODERN GOLONGAN DIURETIK DENGAN TANAMAN HERBALNYA - Indah Sari Amanatun Nisa Indah; Eko Sri Wahyuningsih; Neni Sri Gunarti (Jurnal Buana Farma, 2023)
Hypertension is one of the most common diseases in adults and a risk factor for cardiovascular disease. Hypertension can be said to be a "silent killer" because the patient does not show symptoms before reaching a serious condition or even complications or even death. Hypertension can be treated using 5 classes, namely diuretics, angiotensin converting enzyme inhibitors (ACE Inhibitors), calcium channel blockers (CCB), beta blockers (β Blockers), angiotensinreceptor blockers (ARBs). The aim of this article was to review to find out the types of herbal plants used Has diuretic activity in hypertension. Data search was carried out using Google Scholar and PubMed. Using the keyword "hypertensive diuretic herbal plants". The sources or references obtained are journals from the last 10 years. The results obtained show that there are several herbal plants that have diuretic activity in hypertension, including cucumber (Cucumis sativus L), rosella flowers (Hibiscus sbadariffa), cloves (Syzygium aromaticum L.), tin leaves (Ficus carica L), cat's whiskers (Ortosiphon aristatus), Tomato (Solanum lycipersicum), Celery leaves (Apium graveolens), Soursop (Annona muricata L), Belimbing Wuluh (Averrhoa bilimbi L.), in some of these herbal plants there are chemical compounds that affect the diuretic process and can reduce blood pressure blood, namely Potassium which works by increasing the secretion of sodium, water and chlorine by reducing the volume of blood and extracellular fluid, and the test or method that is carried out can be made in the form of tea, juice, and can be boiled, then drunk the boiled water.